Vertical Distribution of Fish in Surface and Bottom Gill Nets Operated in Gandhisagar Reservoir* - Kartha, K.N.; Rao, K.S. (Fishery Technology, 2025)
The results of studies on the vutical distribution of Catla catla, Labeo rohita, L.Calbasu, Cirrhinus mrigala, Mystus seenghala, Mystus aor, Silonia silondia, and Wallago attu obtained in the surface and bottom operated drift gill nets in Gandhisagar reservoir, are presented.